Pemanfaatan Literasi Digital Di Dunia Pendidikan Era 5.0 - Asnawati Asnawati; Indra Kanedi; Feri Hari Utami; Mirna Mirna; Saira Asmar (Jurnal Dehasen Untuk Negeri, 2023)
The development of the digital world in the world of education in the industrial era 5.0 has affected all aspects of life. digital literacy is the ability to use ICT to find, evaluate, use, create, and communicate information with cognitive and technical skills. The Use of Digital Literacy in the World of Education Era 5.0 among the people has been felt by all people in all corners, both in cities and in villages, both among the general public and students. Utilization of Digital Literacy in the 5.0 Era of Education requires the preparation of competitive human resources through education and training both at school and outside of state vocational high school 1 Kepahiang is a technology-based vocational school, so it is possible that through this school it will generate interest for students to understand and learn the process of Utilizing Digital Literacy in the 5.0 Era of Education. The subjects in this service activity are students state vocational high school 1 Kepahiang district. The output targets to be achieved in community service activities this time are (1) Students of state vocational high school 1 Kepahiang Regency can understand the Utilization of Digital Literacy in the 5.0 Era of Education (2) Students of state vocational high school 1 Kepahiang Regency are able to describe influence, readiness and suitability of industry 4.0 with society 5.0, (3) Students of state vocational high school 1 Kepahiang Regency can find out that through the development and utilization of digital literacy in the era of society 5.0 digital benefits can be obtained in the world of education in the industrial era 5.0, the concept of industry 4.0 and society 5.0 is basically not have a big difference, but the concept of Society is more focused on the context of humans. If the industrial revolution uses AI and artificial intelligence as its main components, while Society 5.0 uses modern technology, it only relies on humans as its main components.